Effect of Astragalus injection on neutrophil gelatinase associated lipocalin level in patients with contrast-induced nephropathy - XIAO Yong-jia; LIU Mei; PENG Da-yan (Linchuang shenzangbing zazhi)
Objective To investigate effect of Astragalus injection on neutrophil gelatinase associated lipocalin(NGAL) level in patients with contrast-induced nephropathy. Methods A total of 64 patients using contrast in the vein and diagnosed with contrast-induced nephropathy from June 2015 to June 2017 were included, and divided into Astragalus group and control group randomly. The patients in the Astragalus group were administered with 20～30 mL Astragalus injection +250 mL physiological saline in a route of intravenous drip, once per day. The patients in the control group were administered with the same amount of physiological saline. Scr and urinary NGAL between the two groups were compared at 24 h, 48 h and 72 h before and after treatment. Results Scr and urinary NGAL levels in the Astragalus group at 24 h, 48 h and 72 h after diagnosis of contrast-induced nephropathy were significantly lower than those in the control group.Conclusions Astragalus injection can significantly reduce Scr and urinary NGAL levels at 24 h, 48 h and 72 h after diagnosis of contrast-induced nephropathy, and protect the kidney.